A Cognitive Perspective on Entrepreneurship and the Firm - Loasby, Brian J. (Journal of Management Studies, 2007)
abstract I propose to examine the theme of this Special Issue from the perspective of its treatment – and, of especial significance, its lack of treatment – within economics. In the course of this examination we shall observe that the concepts of entrepreneurship and the firm are generally kept separate, and attempt to explain why. I shall avoid any discussion of recent work, which is more productively left to my fellow contributors, choosing instead to devote the first half of my contribution to providing an analytical basis for the second half by exploring the problem of knowledge in economic systems, and relating this problem to the evolved nature of human beings and their relationship with their environment. In this exploration I shall rely almost entirely on the work of economists, though much of it was not directed to conventional economic issues.